Information board installed by the Archaeological Survey of India (ASI) - Temples of India Project Team (Jio Institute, 2024)
Information board installed by the Archaeological Survey of India (ASI) written in Hindi and English. The board provides information about the Harshat Mata Temple site and gives a basic introduction to the style of temple construction.